Akantamebni keratitis - Schwarzbartl, Marija Ana (Medicinski razgledi, 1996)
Acanthamoeba is a free-living protozoon. Exposure to acanthamoeba is very common, but infections occur only rarely. Acanthamoeba keratitis should be suspected in every pacient with chronic, progressive ulcerative keratitis of afew weeks' duration, from whom no specific organisms have been isolated, and who fails to respond to conventional antibacterial and antiviral therapy. The therapy is usually long and complicated. Penetrating keratoplasty may be required in cases of unresponsive progressive infection. One patient with chronic progessive acanthamoeba keratitis has been treated at our department so far.
Keywords: medicina; medicine; okužbe; akantameba; očesne bolezni